2023
DOI: 10.1073/pnas.2211631120
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils infiltrate sensory ganglia and mediate chronic widespread pain in fibromyalgia

Abstract: Fibromyalgia is a debilitating widespread chronic pain syndrome that occurs in 2 to 4% of the population. The prevailing view that fibromyalgia results from central nervous system dysfunction has recently been challenged with data showing changes in peripheral nervous system activity. Using a mouse model of chronic widespread pain through hyperalgesic priming of muscle, we show that neutrophils invade sensory ganglia and confer mechanical hypersensitivity on recipient mice, while adoptive transfer of immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 71 publications
(83 reference statements)
0
6
1
Order By: Relevance
“…Supporting this conclusion, we found that (i) systemically administered clodronate and PLX5622 exert opposite effects on neutrophil numbers yet both treatments deplete monocytes and prevent priming; and (ii) local administration of clodronate depletes macrophages from the priming site but has no effect on HP induction. However, the results do not exclude the possibility that neutrophils, which promote widespread persistent nociception in a mouse model of fibromyalgia 81 , might play an ancillary role in HP, as also suggested by the modifications induced in this cell population by IL-6 treatment (present study). Second, our findings identify NAAA as a molecular switch that, when engaged, instructs monocytes to interact with first-order nociceptors and enable priming 19 21 .…”
Section: Discussioncontrasting
confidence: 74%
“…Supporting this conclusion, we found that (i) systemically administered clodronate and PLX5622 exert opposite effects on neutrophil numbers yet both treatments deplete monocytes and prevent priming; and (ii) local administration of clodronate depletes macrophages from the priming site but has no effect on HP induction. However, the results do not exclude the possibility that neutrophils, which promote widespread persistent nociception in a mouse model of fibromyalgia 81 , might play an ancillary role in HP, as also suggested by the modifications induced in this cell population by IL-6 treatment (present study). Second, our findings identify NAAA as a molecular switch that, when engaged, instructs monocytes to interact with first-order nociceptors and enable priming 19 21 .…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, neutrophil infiltration was found in the sensory ganglia of experimental mice. In the same study, neutrophils obtained from FM patients but not from controls and transferred into mice similarly induced diffuse pain syndrome [ 59 , 60 ]. All this evidence suggests that neutrophils may be a potential target in the treatment of FM.…”
Section: The Innate Immune Systemmentioning
confidence: 99%
“…Indeed, the cxcl1 and cxcl2 gene were reported as the most rapidly expressed genes (1 h) at the site of incision in a recent unbiased cell sequencing study ( 168 ). Other studies indicate a role for neutrophils in chronic pain conditions, including fibromyalgia ( 169 ), although how they activate or sensitise nociceptors has not been resolved.…”
Section: Cellular Mechanisms Of Pppmentioning
confidence: 99%